INNOVATIVE MANAGEMENT OF TRUCKING ENTERPRISES (Алматы технологиялық университетінің хабаршысы, 2021)
Conceptions of the stable economy growing of motor-car enterprises are reflected in the article. Principle of dynamic равновесий is used, inculcated О. Моргенштейном, and principle of the system "Канбана" "exactly in time". Application of these rules in service of management motor-car перевозками is comfortable, effective and have good indexes with minimum expenses.